Technology progress on quantum dot light-emitting diodes for next-generation displays. Issue 2 (5th January 2021) - Bang, Sang Yun; Suh, Yo-Han; Fan, Xiang-Bing; Shin, Dong-Wook; Lee, Sanghyo; Choi, Hyung Woo; Lee, Tae Hoon; Yang, Jiajie; Zhan, Shijie; Harden-Chaters, William; Samarakoon, Chatura; Occhipinti, Luigi G.; et al.
Abstract : This article focuses on state-of-the-art technologies used in the research on materials, devices and processes to achieve high-performance QD-LEDs. Abstract : Quantum dot light-emitting diodes (QD-LEDs) are widely recognised as great alternatives to organic light-emitting diodes (OLEDs) due to their enhanced performances. This focus article surveys the current progress on the state-of-the-art QD-LED technology including material synthesis, device optimization and innovative fabrication processes. A discussion on the material synthesis of core nanocrystals, shell layers and surface-binding ligands is presented for high photoluminescence quantum yield (PLQY) quantum dots (QDs) using heavy-metal free materials. The operational principles of several types of QD-LED device architectures are also covered, and the recent evolution of device engineering technologies is investigated. By exploring the fabrication process for pixel-patterning of QD-LEDs on an active-matrix backplane for full-colour display applications, we anticipate further improvement in device performance for the commercialisation of next-generation displays.